Exploring Ecoprint-Based Media: Enhancing Fine Motor Skills in Early Childhood Education - Bachtiar, Muhammad Yusri; Hasmawaty , Hasmawaty; sultan, jumriani; AM, Muh Asriasi; Kassymova, Gulzhaina K. (JURNAL PENDIDIKAN USIA DINI, 2025)
Fine motor skills are an important aspect in early childhood development, but are often not optimal due to limited interesting and effective learning methods. This study aims to analyze the effect of ecoprint activity-based learning media methods on fine motor skills in early children. The research method used is quantitative with a quasi-experimental design using two groups, namely the experimental group and the control group with a sample size of 20 children. Data analysis used the Wilcoxon Signed Ranks Test which is a non-parametric statistical test. The results showed a significant increase in children's fine motor skills in the experimental group compared to the control group. In the experimental group, 60% reached the category of "very well developed" on the indicators of eye-hand coordination, movement accuracy, and self-expression. Ecoprinting activities involving natural materials such as leaves and flowers have been proven effective in training children's fine motor skills through a fun creative process. Therefore, this method is recommended for early childhood learning to improve children's fine motor skills, creativity, and environmental awareness